RANCANGAN SISTEM ABSENSI KARYAWAN BERBASIS WEBSITE PADA PT BARUMAN JAYA PERKASA - Rayhan Cesario; Fathir Mohammad Noer; Yodis Saputra; Achmad Lutfi Fuadi (Journal of Research and Publication Innovation, 2025)
This study discusses the design of a web-based attendance system to address inefficiencies in the manual attendance process at PT Baruman Jaya Perkasa. The system was developed using PHP as the programming language, MySQL for data storage, and CodeIgniter as the framework, applying the Waterfall development model. Key features include role-based login, employee data management, real-time attendance recording, and automated report generation in PDF format. The implementation results indicate the system's ability to improve data accuracy, operational efficiency, and accessibility for HR and management.